ECONOMIC CYCLES AND THE THERMODYNAMIC UNCERTAINTY RELATIONS - Parker, Edgar (The journal of contemporary issues in business and government, 2024)
In the century and a half since Maxwell first conjured his “finite being” which Lord Kelvin subsequently dubbed a “daemon”, researchers have explored the connections between non-equilibrium thermodynamics, entropy, and information theory. In recent years various Thermodynamic Uncertainty Relations (TURs) have been derived to inform upon the relationship between the entropy production and the precision possible in thermodynamic machines and processes. In this paper the recently derived TURs are applied to a hypothetical thermodynamic economy. The TURs define the lower bound on the total entropy production of the economy. Changes in the economy’s entropy production rate have important consequences for the stability of the economic systems, the growth of inflation and play a central role in the evolution of the business cycle. This new perspective has important implications for policy makers, researchers, and other economic actors.